Food Stocks as a Food Security Factor: Theoretical and Methodological Aspects - M.Yarkova, Tatiana (2021)
The issue of food security is a pressing one for the entire global community. This problem must be solved together at the expense of the resource capacity of countries that have sufficient or predominant agrarian specialisation to produce staple foods. Food security is ensured by favourable assessment criteria of the physical and economic accessibility of staple foods to the population.